Mediated Lives: digital technologies and the body - Anabela da Conceição Pereira (2nd European Conference on the Impact of Artificial Intelligence and Robotics, ECIAIR 2020, 2020)
Starting from a re-visitation of the classical mind-body philosophical problem, this poster presentation was a discussion of the mental and physical effects of the uses of digital technologies for the body, namely possible alterations in the brain structure and neuroplasticity, as well as a discussion of their social consequences.